Influence of the environment and the host on parasitization by Varroa jacobsoni Oud - García Fernández P. (The varroosis in the Mediterranean region, 1997)
This is a review of the influence of external factors, such as climate and phenology, and some intrinsic factors, such as host specificity, adaptation to parasitism, etc., on Varroa jacobsoni parasitization of the honey bee. This ectoparasitic mite of the Asian bee (A. cerana) has been invading new hosts, species, subspecies and races of bee in a progressive expansion that has led to this disease becoming a real pest for bee-keepers practically world-wide. The influence of various ecosystems and hosts on the development of this mite has led to a different pattern in its population dynamics. V. jacobsoni was well adapted to its original host (A. cerana), but when it infected other honey bee species, which live in different geographical and climatic conditions, these show a different susceptibility to the mite. Over the last thirty years there has been a great deal of research into the development of V. jacobsoni according to its different geographical location, its infestation of species, subspecies and races of honey bees, their intrinsic characteristics (sex, age, behaviour, etc.) and tolerance of the mite, and the existing climate and seasonal patterns. However, more local studies should be made on the development of the parasite in the different races and subspecies of bees that inhabit the Mediterranean basin, which is the region that concerns us here.
Seminar on The Varroosis in the Mediterranean Region, 1996/09/22-23, Granada (Spain)